Turkish Germans in Turkiye From their children's perspective - Topdemir Kocyigit, Oya (Istanbul University Press, 2022)
This book is a revised version of my doctoral dissertation titled "Transnational Experiences and the Meaning of Being 'Turkish-German'". I presented it at Istanbul University, Institute of Social Sciences, Department of Anthropology in 2017. It was based on the ethnographic fieldwork I conducted in Turkiye. I interviewed 45 people whose mothers were German and fathers Turkish. I found the participants using the snowball method. I carried out the research using the in-depth interview and participant observation technique. Thirty-one of them were women and the others were men. In this research, I aimed to reveal how the family experiences of parents with different cultural backgrounds are evaluated by their children. In other words, I studied how being in a transnational family was perceived across generations. There are not many studies in the literature showing the cultural dimensions of marriages, which have gradually increased between Turkish and German citizens, that focus on their children. This research includes striking findings in terms of war memory, high-skilled migrants and return migration, and experiences of transnational family, kinship, and identity, which are important phenomena in our present time. The research also reveals a transnational and unwritten common cultural history between Turkiye and Germany through mixed marriages that have increased as of the 1930s. The book aims to make an original and important contribution to the national and international literature in terms of being based on ethnographic research, the framework of the subject, the sample (which also reflects the evaluations of different generations and siblings), and the results. It embodies the fact that the identity constructions of today's "Turkish German" generation in Turkiye are closely related to the experiences of war, migration, and kinship that occupy an important place in familial memory. As the children recounted their life stories, they focused on the familial experiences that largely shaped their personal stories. Among these experiences, especially from the Second World War (WWII), migration between Turkiye and Germany and kinship practices were the subjects that children focused on the most. I was able to see how they made sense of these experiences, and on the other hand, I had the opportunity to understand how they construct their own identities based on these meanings. As an anthropologist, it was unique for me to see the relationship between personal experiences, identification processes, and the histories of several previous generations.